2019
DOI: 10.1097/iae.0000000000002164
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Outcomes of Intravitreal Ranibizumab for Choroidal Neovascularization in Patients With Pathologic Myopia

Abstract: Intravitreal ranibizumab provide a 5-year visual benefit in eyes with myopic CNV compared with the natural course. A lack of enlargement of the CNV-related macular atrophy, a better baseline BCVA, and a minimum number of IVR injections were associated with better visual outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 21 publications
2
20
1
Order By: Relevance
“…This defect in Bruch's membrane may continue to expand in spite of adequate treatment of myopic CNV, leading to macular atrophy and loss of vision [16]. This point was demonstrated in a 5-year outcome study of eyes with myopic CNV treated with intravitreal ranibizumab (n = 51), in which visual stability was achieved (baseline best corrected visual acuity 20/49 compared to 20/42) at 5 years, where good visual outcome was shown to be significantly associated with a lack of enlargement of CNVrelated macular atrophy, in addition to better baseline visual acuity and a lower number of injections [79]. These outcomes were achieved with a mean of 1.6 injections over 5 years, and two-thirds received only 1 injection.…”
Section: Long-term Outcomesmentioning
confidence: 92%
See 1 more Smart Citation
“…This defect in Bruch's membrane may continue to expand in spite of adequate treatment of myopic CNV, leading to macular atrophy and loss of vision [16]. This point was demonstrated in a 5-year outcome study of eyes with myopic CNV treated with intravitreal ranibizumab (n = 51), in which visual stability was achieved (baseline best corrected visual acuity 20/49 compared to 20/42) at 5 years, where good visual outcome was shown to be significantly associated with a lack of enlargement of CNVrelated macular atrophy, in addition to better baseline visual acuity and a lower number of injections [79]. These outcomes were achieved with a mean of 1.6 injections over 5 years, and two-thirds received only 1 injection.…”
Section: Long-term Outcomesmentioning
confidence: 92%
“…Although anti-VEGF therapy for myopic CNV has demonstrated remarkable short-and mid-term efficacy, longer term visual outcomes are generally less favorable, with most studies reporting a gradual decline back to baseline visual acuity [60,61,[75][76][77][78][79]. Onishi et al reported the 5-year outcomes of 51 patients who received treatment with ranibizumab for myopic CNV.…”
Section: Long-term Outcomesmentioning
confidence: 99%
“…With the advancement of such OCT technology, research on myopic macular diseases such as RS and mCNV, which are directly related to decreased visual function, has progressed dramatically. Studies using OCT have shown that early surgical intervention is important for the maintenance of long-term visual function in the context of RS [10][11][12][13][14][15] and that early anti-vascular endothelial growth factor drug administration can help to maintain long-term visual function in mCNV [16][17][18][19][20]. Therefore, early detection and treatment of macular lesions associated with myopia are crucial to maintaining better vision.…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement of such OCT technology, research on myopic macular diseases such as RS and mCNV, which are directly related to decreased visual function, has progressed dramatically. Studies using OCT have shown that early surgical intervention is important for the maintenance of long-term visual function in the context of RS [1015] and that early anti–vascular endothelial growth factor drug administration can help to maintain long-term visual function in mCNV [1620]. Therefore, early detection and treatment of macular lesions associated with myopia are crucial to maintaining better vision.…”
Section: Introductionmentioning
confidence: 99%